2010
DOI: 10.1002/jcla.20328
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to DNA and lipids: correlation with protein glycation in patients with type 1 diabetes

Abstract: Diabetic hyperglycemia is associated with increased production of reactive oxygen species (ROS). ROS reacts with DNA resulting in various products, such as 8-hydroxydeoxyguanosine (8-OHdG), that excrete in urine owing to DNA repair processes. Urinary 8-OHdG has been proposed as an indicator of oxidative damage to DNA. This study aimed to evaluate relationship between oxidative damage to DNA and protein glycation in patients with Type 1 diabetes. We measured urinary 8-OHdG level in diabetic patients and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…Diabetes and elevated levels of arginase activity and expression are associated with increased levels of ROS (15). Our study showed that whole body levels of ROS are elevated in diabetic WT mice, as indicated by measurements of plasma lipid hydroperoxide levels.…”
Section: Rossupporting
confidence: 58%
“…Diabetes and elevated levels of arginase activity and expression are associated with increased levels of ROS (15). Our study showed that whole body levels of ROS are elevated in diabetic WT mice, as indicated by measurements of plasma lipid hydroperoxide levels.…”
Section: Rossupporting
confidence: 58%
“…18,19 Increased oxidative stress induced by hyperglycemia may contribute to the pathogenesis of diabetic complications including nephropathy. 20 Diabetic hyperglycemia is associated with increased production of reactive oxygen species. 20 Reactive oxygen species damage to DNA necessitates the induction of various DNA repair processes, which can result in the urinary excretion of products such as 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…20 Diabetic hyperglycemia is associated with increased production of reactive oxygen species. 20 Reactive oxygen species damage to DNA necessitates the induction of various DNA repair processes, which can result in the urinary excretion of products such as 8-OHdG. 21 Urinary 8-OHdG is therefore a sensitive biomarker of oxidative DNA damage, and is also significantly correlated with the severity of tubulointerstitial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted in Type 2 diabetes mellitus (n=60) and controls (n=60) indicated that oxidative stress ratio and DNA damage was found to be increased in patients than in controls [40]. A study conducted among Bangladeshi population has also reported that DNA damage is closely [42]. A study conducted in Mexican population indicated a lack of association between diabetes and DNA damage [43].…”
Section: Association Between Tas Dna Damage and Type 2 Diabetes Melmentioning
confidence: 98%